Games of Collaboration: An Ethnographic Examination of Experts Acting Seriously - Reed, Adam (Suomen Antropologi: Journal of the Finnish Anthropological Society, 2024)
This paper looks at the theme of collaboration through the prism of game design, and especially the example of serious games. At its heart, this is a consideration of two collaborative projects between experts. The first is a current collaboration between computer scientists, game designers, and a theatre company in Scotland, in which the author is also a collaborator and the project’s ethnographer. The second is perhaps the largest and most high-profile collaborative project recently led and documented by anthropologists, Meridian 180, which aims to experiment with the norms of collaboration itself, and which has already been theorised and extensively reflected upon by one of its founders, Annelise Riles. The paper aims to put these two collaborations into some kind of conversation in order to throw each into productive relief and to ask some new questions about how we think about both the exercise of collaboration and the deliberate subversion of its norms. Keywords: collaboration, serious games, co-operation, experts, rules, friendship